Implementasi Push Notification Pada Mobile Application Untuk Absensi Siswa Berbasis Android Dengan Firebase Cloud Messaging (Studi Kasus: TK Islam Daarul Fatwa) - Dila Fadilah; Hadi Zakaria (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Daarul Fatwa Islamic Kindergarten is a Kindergarten school that organizes Education Programs for children aged 4-6 years. In its teaching system, Daarul Fatwa Islamic Kindergarten introduces how to write, read the Koran and introduces the procedures for worship and Islamic history, where teaching reading the Koran from an early age is the main program to shape the Islamic personality in each of its students. One of the assessments in learning at Daarul Fatwa Islamic Kindergarten is assessed from attendance or attendance, but the attendance system used by Daarul Fatwa Islamic Kindergarten still uses paper sheets, where a system like this still has many shortcomings such as student attendance information cannot be monitored in real time by the teacher and student parents. In overcoming this problem, the author conducted a study to create an Android-based student attendance application with push notifications to make it easier for teachers to process attendance data and recapitulation in real time to parents so that parents do not need to feel anxious and worried about the presence of their sons and daughters at school. In this writing, the author uses a programming language, namely Java and Android Studio as a text editor, as well as a MySQL database as student attendance data storage and the Waterfall Model as the design flow. It is hoped that this student attendance system can simplify the attendance process and deliver real-time information that can assist teachers in processing attendance data, and can provide information to parents.